Avoiding entry into intracellular protein degradation pathways by signal mutations increases protein secretion in Pichia pastoris. Issue 9 (3rd June 2022) - Ito, Yoichiro; Ishigami, Misa; Hashiba, Noriko; Nakamura, Yasuyuki; Terai, Goro; Hasunuma, Tomohisa; Ishii, Jun; Kondo, Akihiko
Summary: In our previous study, we serendipitously discovered that protein secretion in the methylotrophic yeast Pichia pastoris is enhanced by a mutation (V50A) in the mating factor alpha (MFα) prepro‐leader signal derived from Saccharomyces cerevisiae . In the present study, we investigated 20 single‐amino‐acid substitutions, including V50A, located within the MFα signal peptide, indicating that V50A and several single mutations alone provided significant increase in production of the secreted proteins. In addition to hydrophobicity index analysis, both an unfolded protein response (UPR) biosensor analysis and a microscopic observation showed a clear difference on the levels of UPR induction and mis‐sorting of secretory protein into vacuoles among the wild‐type and mutated MFα signal peptides. This work demonstrates the importance of avoiding entry of secretory proteins into the intracellular protein degradation pathways, an observation that is expected to contribute to the engineering of strains with increased production of recombinant secreted proteins. Abstract : Several single‐amino‐acid substitutions, including a serendipitously discovered mutation V50A, located within the mating factor alpha (MFα) prepro‐leader signal peptide provided significant increase in production of the secreted proteins in Pichia pastoris . Our unfolded protein response (UPR) biosensor analysis and microscopic observation showed a clear difference on the levels of UPR induction and mis‐sorting of secretory protein into vacuoles among the wild‐type and mutated MFα signal peptides, indicating that the importance of avoiding entry of secretory proteins into the intracellular protein degradation pathways lead to the engineering of strains with increased production of recombinant secreted proteins.